Las fábulas en el desarrollo de los valores morales en niños y niñas de 4 a 5 años de edad del paralelo “C” en la unidad educativa Ángel Polibio chaves de la ciudad de Guaranda, provincia Bolívar, período 2023- 2024. - Lema Ortiz, Cristhina De Los Ángeles (2024)
Moral values are main part in the formation of the human being and are inculcated first in the home and strengthened in the school, nowadays they aren`t promoted and cause problems in the social performance of the human being, therefore in this project titled "Fables in the development of moral values in children from 4 to 5 years of age in the parallel “C” in Unidad Educativa Ángel Polibio Cháves in Guaranda city, Bolívar province, period 2023-2024" the main objective is to use children's fables as a strategy to promote moral values in children. In this way, the aim is to promote moral values using fables as a didactic resource for teaching and learning process of children, with the purpose of generate critical thinking that causes them to consider the behavior that the characters perform in the story, also through the moral advice gives them a life lesson where it will allow them to reflect on the different behaviors that experience in their daily lives. It is important to highlight that the objectives established in the investigation project seek to determine how fables benefit the development of good morals in boys and girls, therefore, to know what is the level of knowledge that children have about moral values; developing a didactic guide in which important values for the lives of human beings will be reflected. For these reasons, it is important to encourage the habit of reading in children from an early age, where through fables they will learn to differentiate between good and bad using moral values, also giving a special part to stimulating the imagination and improving their behavior and decisions, and an interview that will be applied to the population to collect necessary information in order to implement our project objectively